2014
DOI: 10.1038/hdy.2013.121
|View full text |Cite
|
Sign up to set email alerts
|

Tempo and mode of recurrent polyploidization in the Carassius auratus species complex (Cypriniformes, Cyprinidae)

Abstract: Polyploidization is an evolutionarily rare but important mechanism in both plants and animals because it increases genetic diversity. Goldfish of the Carassius auratus species complex can be tetraploids, hexaploids and octaploids. Polyploidization events have occurred repeatedly in goldfish, yet the extent of this phenomenon and its phyletic history are poorly understood. We explore the origin, tempo and frequency of polyploidization in Chinese and Japanese goldfish using both mitochondrial (mtDNA) and nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 57 publications
4
58
2
1
Order By: Relevance
“…A total of 3,105 individuals of the Carassius species complex were currently sampled from 34 locations through mainland China. And the other 1,054 sample data of Carassius species complex from 15 localities in East Asia were collected from previous reports (Luo et al., ; Takada et al., ). Details about all the samples, sampling sites, and references are given in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 3,105 individuals of the Carassius species complex were currently sampled from 34 locations through mainland China. And the other 1,054 sample data of Carassius species complex from 15 localities in East Asia were collected from previous reports (Luo et al., ; Takada et al., ). Details about all the samples, sampling sites, and references are given in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Tetraploids with 100 chromosomes are diploidizated allotetraploids that reproduce by sexual reproduction (Luo, Stadler, He, & Meyer, ; Ohno, Muramoto, Christian, & Atkin, ), while hexaploids with about 150 chromosomes are able to reproduce by dual modes including unisexual gynogenesis and bisexual reproduction (Gui & Zhou, ; Gui & Zhu, ; Zhou, Wang, & Gui, ), and octaploids reproduce only via unisexual gynogenesis (Xiao et al., ; Zhu & Gui, ). Recently, an early allopolyploidy event leading to ancestral allotetraploids has been revealed, and a recurrent autopolyploidy from allotetraploids that results in allohexaploids has been elucidated in the Carassius species complex (Li, et al., ; Luo et al., ). Therefore, the wide geographic distribution, coexistence of different ploidy forms, and occurrence of repeated polyploidy events make the Carassius species complex an ideal system to investigate evolutionary trajectory and ecological adaption of polyploidy in vertebrates (Gao et al., ; Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, to date, there was no direct genetic evidence for this. Although analyses of both mitochondrial and nuclear DNA sequences have revealed that recurrent autoploidization occurs in all sampled populations of the C. auratus complex (Luo et al, 2014), our most important finding was the direction of cytogenetic evidence for the autotriploid origin of C. auratus with 150 chromosomes. What was the possible origin of the autotriploid forms in the C. auratus complex?…”
Section: Discussionmentioning
confidence: 76%
“…Thus, it has been assumed that C. carpio and C. auratus have undergone a fourth round of genome duplication (Luo et al, 2007;Wang et al, 2012). In recent years, many studies have revealed that polyploid C. auratus have undergone several successive rounds of genome polyploidy and that they have experienced an additional, more recent genome duplication event (Gui and Zhou, 2010;Li et al, 2014;Luo et al, 2014). In the Dongting water system, the C. auratus complex is characterized by the coexistence of diploids (2nCC) and polyploids (3nCC and 4nCC), which are quite similar morphologically but differ markedly in their modes of reproduction (Koboyasi, 1971;Mezhzherin and Kokodiy, 2010;Yang et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation